2011
DOI: 10.3390/f2040814
|View full text |Cite
|
Sign up to set email alerts
|

Regional Models of Diameter as a Function of Individual Tree Attributes, Climate and Site Characteristics for Six Major Tree Species in Alberta, Canada

Abstract: Abstract:We investigated the relationship of stem diameter to tree, site and stand characteristics for six major tree species (trembling aspen, white birch, balsam fir, lodgepole pine, black spruce, and white spruce) in Alberta (Canada) with data from Alberta Sustainable Resource Development Permanent Sample Plots. Using non-linear mixed effects modeling techniques, we developed models to estimate diameter at breast height using height, crown and stand attributes. Mixed effects models (with plot as subject) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Diameter at breast height Cortini et al (2011), Filipescu et al (2012 Maximum branch diameter Groot and Schneider (2011) Sapwood area distribution (longitudinal) Cruickshank et al (in review) Ring area distribution (longitudinal) Cortini et al (2013) Wood density, microfibril angle, Cortini et al (2014) Attribute variation in three dimensions is ignored when dimensionality is reduced by restricting measurements to only part of the tree. For example, measurements of wood density at the breast height part of the stem do not take into account any vertical dependence of this property and may provide a poor indication of wood density over the entire tree (Repola 2006).…”
Section: Fibre Attribute Publicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diameter at breast height Cortini et al (2011), Filipescu et al (2012 Maximum branch diameter Groot and Schneider (2011) Sapwood area distribution (longitudinal) Cruickshank et al (in review) Ring area distribution (longitudinal) Cortini et al (2013) Wood density, microfibril angle, Cortini et al (2014) Attribute variation in three dimensions is ignored when dimensionality is reduced by restricting measurements to only part of the tree. For example, measurements of wood density at the breast height part of the stem do not take into account any vertical dependence of this property and may provide a poor indication of wood density over the entire tree (Repola 2006).…”
Section: Fibre Attribute Publicationsmentioning
confidence: 99%
“…The CFAR project demonstrated that DBH for a number of Canadian species can be estimated from tree height, crown characteristics, and stand and site attributes using non-linear equations with a typical RMSE of about 10%-15% (Cortini et al 2011, Filipescu et al 2012. Subsequent research in other jurisdictions has also used non-linear DBH-height relationships (Bi et al 2012), and included crown variables such as crown diameter in models (Gonzalez-Benecke et al 2014, Balenovic et al 2015.…”
Section: Progress In Predicting Dbh From Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some cases, inclusion of additional variables (e.g., stand density, stand age, soil type, elevation, etc.) may considerably improve the estimates [12][13][14]. For example, Prieditis et al [14] built a model with tree height as the only independent variable which provides reasonably accurate estimates of DBH (R 2 = 0.792), but when the crown diameter and information about tree age and soil type obtained from existing forest database were added to the model, the accuracy of DBH increases (R 2 = 0.872).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, which and how many independent variables should be used in allometric equations are very important issues in modeling of tree characteristics. Estimation models may be built using field measurement [4][5][6]13,14] or combination of field and remote sensing measurement [8,9]. In that case positions of trees in the field have to be measured with high precision and determined on remote sensing data which often is not easy [10].…”
Section: Introductionmentioning
confidence: 99%